Literature Review: Variant of Kratom (Mitragyna speciosa (Korth.) Havil) in West Kalimantan - Rahmad Rahmad; Bagus Pratomo Nusantoro; Reza Reza; Zidan Hafidz Al Awwali (Jurnal Biologi Tropis, 2026)
Kratom is a plant with potential biological diversity. This plant can grow in tropical areas with humid conditions, which is why it can be found in West Kalimantan and is known by the local people as purik leave. The purpose of this research is to summarize information related to kratom variant and provide a comprehensive overview of the presence of kratom plant in West Kalimantan. This research used a literature review method, focusing on national and international journals from the last 10 years accessed with Google Scholar with the help of the Publish or Perish search application. The search results show that there are three kratom variant in West Kalimantan namely red vein, white vein, and green vein, variant which can be distinguished by specific difference in color and leaf vein characteristics. Variant of kratom show their own distinctive characteristics even though these three variant are still within the same kratom species the scientific name Mitragyna speciosa (Korth.) Havil. This research is expected to serve as a source of the information and reference that can research related to kratom plant.